Extraction of Palm Carotenes and Effect of Oxidative Degradation on β-carotene - Suria, Kupan; Kulkarni, Ajaykumar D.; Hazrulrizawati, Hamid; M. M., Yusoff (ESRSA Publications Pvt. Ltd., 2015)
The growing demand on beta-carotene has generated huge challenges to global industry to fulfill the customers’ requirement that are looking for natural and environment friendly products. This study explains the efficient extraction of carotenoids from Crude Palm Oil by adsorption (column chromatography) where in the suitability of adsorbent is discussed and saponification methods followed by degradation of beta-carotene in an attempt to study the possible norisoprenoids that can be potentially generated using palm carotene in future. The HPLC analysis showed the high concentration of beta-carotene in extracted samples. Gas chromatography/mass spectrometric (GC-MS) analysis showed that, the main degraded compound generated were β-ionone,DHA and ionone epoxide.